Sensitivity of cells to apoptosis induced by iron deprivation can be reversibly changed by iron availability - Koc, M; Nad'ová, Z; Kovár, J (Cell proliferation, 2006)
We tested the effect of iron deprivation on cell death induction in human Raji cells pre-adapted to differing availability of extracellular iron. Iron deprivation was achieved by incubation in a defined iron-free medium. Original Raji cells have previously been adapted to long-term culture in a defined medium with 5 microg/ml of iron-saturated human transferrin as a source of iron. Raji/lowFe cells were derived from original Raji cells by subsequent adaptation to culture in the medium with 50 microm ferric citrate as a source of iron. Raji/lowFe-re cells were derived from Raji/lowFe cells by re-adaptation to the transferrin-containing (5 microg/ml) medium. Iron deprivation induced cell death in both Raji cells and Raji/lowFe-re cells; that is, cells pre-adapted to a near optimum source of extracellular iron (5 microg/ml of transferrin). However, Raji/lowFe cells preadapted to a limited source of extracellular iron (50 microm ferric citrate) became resistant to the induction of cell death by iron deprivation. We demonstrated that cell death induction by iron deprivation in Raji cells correlates with the activation of executioner caspase-3 and the cleavage of caspase-3 substrate, poly-ADP ribose polymerase. Two other executioner caspases, caspase-7 and caspase-6, were not activated. Taken together, we suggest that in human Raji cells, iron deprivation induces apoptotic cell death related to caspase-3 activation. However, the sensitivity of the cells to death induction by iron deprivation can be reversibly changed by extracellular iron availability. The cells pre-adapted to a limited source of extracellular iron became resistant.
Keywords: nádorové buněčné linie; apoptóza; Iron Deficiencies; lidé; kaspasa 3; Burkittův lymfom; deficit železa; buněčné dělení; kaspasa 6; Cell Division; železo; Cell Line, Tumor; Burkitt Lymphoma; kaspasa 7; Enzyme Activation; Iron; Caspase 3; Humans; Caspase 7; viabilita buněk; aktivace enzymů; kultivační média; Cell Survival; Caspase 6; Apoptosis; Culture Media